2013
DOI: 10.1111/cen.12069
|View full text |Cite
|
Sign up to set email alerts
|

Volume interpolated 3D‐spoiled gradient echo sequence is better than dynamic contrast spin echo sequence for MRI detection of corticotropin secreting pituitary microadenomas

Abstract: VI-SGE MR sequence was better for localization of pituitary microadenomas particularly when DC-SE MR sequence is negative or equivocal and should be used in addition to DC-SE MR sequence for the evaluation of ACTH-dependent CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 18 publications
4
36
0
2
Order By: Relevance
“…However, most patients with ACTH-dependent Cushing’s syndrome have an occult (i.e., hidden) tumor. Pituitary adenomas can be very small and be missed by even the most advanced magnetic resonance scanning techniques described below (123,194,278). Furthermore, ectopic ACTH-secreting neuroendocrine tumors (e.g., bronchial carcinoids) can be small ( < 1 cm) and difficult to identify in imaging studies.…”
Section: Clinical Features Of Cushing’s Syndromementioning
confidence: 99%
“…However, most patients with ACTH-dependent Cushing’s syndrome have an occult (i.e., hidden) tumor. Pituitary adenomas can be very small and be missed by even the most advanced magnetic resonance scanning techniques described below (123,194,278). Furthermore, ectopic ACTH-secreting neuroendocrine tumors (e.g., bronchial carcinoids) can be small ( < 1 cm) and difficult to identify in imaging studies.…”
Section: Clinical Features Of Cushing’s Syndromementioning
confidence: 99%
“…13,16 However, differential enhancement within the pituitary gland may best be visible during the first 10 to 20 seconds. 10 The ESC can potentially allow the fast acquisition of higher resolution sellar images.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining higher resolution images during dynamic imaging may improve the detection of smaller adenomas by preventing the tissue averaging seen in thicker slices. 13,24 …”
Section: Discussionmentioning
confidence: 99%
“…Another concern is the MR image quality of the current study. Previous studies reported exhibiting 66%-100% sensitivity in detecting ACTHsecreting microadenoma 6,7 with the aid of DCE-MR imaging. The sensitivity of the current study for detecting ACTH-secreting microadenomas was as low as 32%, which may suggest that MR images of the current study might have been suboptimized compared with the past literature reports.…”
Section: Discussionmentioning
confidence: 99%